Estudio de la importancia y beneficio de la ley de transparencia y acceso a la información pública en la zona norte de la provincia de Manabí - Álava Rade, Mariano Raphael (2015)
This study was developed with the objective of diagnose the fulfillment of the Organic Law of Transparency and Access to Public Information (LOTAIP) in the northern part of the province of Manabi. On the object of study was the survey as an instrument for gathering quantitative data on the samples of the population of the cantons Bolivar, Chone, El Carmen, Flavio Alfaro, Jama, Pedernales, San Vicente and Tosagua to identify the level of knowledge about the law, the need for publication of information and media access. The interview was also applied to all legal representatives of Governments Autonomous Decentralized Municipal (GAD), branches of the National Bank of Development (BNF) and Registrations of the Property corresponding to the jurisdictions before mentioned; this technique had order to collect qualitative data on the warranty provided to citizens to access public information efforts, the means used for its publication and ease of participation in the decisions of general interest. Statistical processing was performed in Excel, with the results that the 74,80% unknown the LOTAIP, the 76,50% has had no information about the entities studied law and the 83,09% is not aware of how to access the web pages of these and other institutions. On the other hand was determined that only the BNF in all their branches publishes 100% parameters set out in article 7 of the LOTAIP. It is concluded that still spread the law, comply with advertising of the information required and thus make effective citizen participation in decisions of general interest.